Gradientes funcionais em galhas induzidas por Pseudophacopteron longicaudatum (HEMIPTERA) em Aspidosperma tomentosum Mart. (APOCYNACEAE): Composição da parede celular e metabólitos - Martini, Vitor Campana (2017)
Galls insects are capable to alter plants tissues to a different future, and create a new organ called gall. The stress made by this biotic interaction involves a chain of modifications in the conformations and composition of the cell wall, changing citologic and histochemistry patterns from his host, what increase the adaptativa value of the insect. Pseudophacopteron longicaudatum (Hemiptera: Psyllidae) induce gall in Aspidosperma tomentosum (Apocynaceae), the development infested tissue start hypertrophy and hyperplasia, forming an oval gall, and, is expected to have citologic, histochemistry gradient, and a fotosynthetic change, as observed in others neotropical systems. The injure made by the gall insect during the gall development alters the citologic and histochemistry patterns from the host, boosting the cell activity close to ninfa feeding area. The photosynthetic yield seems to be weakened, and the cell wall presents HGAs high metylesterified. Although the photosyntesis is weakened and parenchyma is formed, Pseudophacopteron longicaudatum (Hemiptera: Psyllidae) induced galls don’t configure as a photoassimilated drain.